THE EFFECT OF VISUAL NOVEL BASED PC GAME: FRUIT AND VEGGIE STORY TO INCREASE KNOWLEDGE, FRUIT AND VEGETABLE CONSUMPTION AMONG SCHOOL-AGED CHILDREN - Susana Widyaningsih (Universitas Pahlawan, 2022)
Lack of knowledge regarding fruit and vegetable could result in low consumption of those food among Indonesian children. A PC game named Fruit and Veggie Story that we have developed could act as an educational means for children to learn about the importance of consuming fruit and vegetable in a pleasant way. This study aimed to measure the effectiveness of Visual Novel PC Game: Fruit & Veggie Story to increase knowledge as well as fruit and vegetable consumption among school-aged children. This study was a quasi-experiment two groups with pre-post tests. 50 students from class 2A and 2B at SD Muhammadiyah Bumiayu were assigned into experiment and control groups. After playing the game daily for a week, respondents in the experiment group were measured over their knowledge using a questionnaire consisting of 10 MCQ questions. Moreover, after one week period, the students’ consumption was measured using a food recall diary. The data were presented in frequency, percentage and analysed using paired T-test and independent T-test. The results showed that the average knowledge score before the intervention was 5.76, while after the intervention it increased to 8.12. The average of fruit and vegetable consumption before the intervention was 463.20 grams and after the intervention it increased to 577.44 grams (P= 0.000). The Fruit and Veggie Story PC game is a technology innovation in education to effectively increase knowledge regarding fruit and vegetable. It is also able to encourage children to eat more of those food. Key words: PC game, fruit and vegetable consumption